An Integrated Model of Customer Loyalty in Automobile Insurance in Thailand - Meeboonsalang, Wanngam (Animo Repository, 2019)
Factors influencing customer loyalty toward automobile insurance companies in Thailand were examined, and a structural equation model of variables was analyzed. A questionnaire was employed to gather primary data. Survey participants included 549 customers of automobile insurance companies in Thailand derived from multi-stage sampling. Data were analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM). Findings revealed that service quality, brand image, and customer commitment had a positive impact on customer loyalty, with perceived value and customer trust showing a negative impact. Service quality had a strong impact on customer satisfaction, which had no direct effect on customer loyalty. Perceived value could lead to customer satisfaction. No relationship was found between the brand image and customer satisfaction.